2007
DOI: 10.1214/009053606000001316
|View full text |Cite
|
Sign up to set email alerts
|

Rank-based estimation for all-pass time series models

Abstract: An autoregressive-moving average model in which all roots of the autoregressive polynomial are reciprocals of roots of the moving average polynomial and vice versa is called an all-pass time series model. All-pass models are useful for identifying and modeling noncausal and noninvertible autoregressive-moving average processes. We establish asymptotic normality and consistency for rank-based estimators of all-pass model parameters. The estimators are obtained by minimizing the rank-based residual dispersion fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Using a proof similar to that of Lemma 16 on page 88 of Andrews (2003), it can be shown that sup x∈I R |f n (x) − f n (x)| P → 0, and so this lemma holds.…”
Section: Garch Modelingmentioning
confidence: 88%
See 1 more Smart Citation
“…Using a proof similar to that of Lemma 16 on page 88 of Andrews (2003), it can be shown that sup x∈I R |f n (x) − f n (x)| P → 0, and so this lemma holds.…”
Section: Garch Modelingmentioning
confidence: 88%
“…The weight function λ t7 is plotted in Figure 3.1, along with λ N . Note that λ t7 (x) and λ N (x) are fairly similar except near x = 1. relatively efficient (see, for example, Hettmansperger and McKean, 1998, Andrews, Davis, and Breidt, 2007, and Andrews, 2008. In the case of linear model estimation, λ W is the optimal weight function when the noise distribution is logistic and, for R-estimation of GARCH model parameters, λ W is optimal when ln(Z 2 t )…”
Section: Limiting Distribution For R-estimatorsmentioning
confidence: 99%
“…For instance, it has been extensively studied in the time series literature (e.g., Andrews et al (2007);Hill (2015)). The quantile regression is another type of robust estimation.…”
Section: Further Related Literature Organization and Notationmentioning
confidence: 99%
“…Processes which are second order uncorrelated or white but with higher order dependence occur often in financial data. The estimation of parameters of such all-pass ARMA models using least absolute deviations is given in [8], using maximum likelihood in [1] and using rank based procedures in [2]. The rank based method can have the same asymtotic efficiency as maximum likelihood estimators and are robust to some distributional assumptions.…”
Section: If the Output Process {X(t)} Is Observed With An Independentmentioning
confidence: 99%